A Meta‐Analysis and Systematic Review on the Global Prevalence, Risk Factors, and Outcomes of Coronary Artery Disease in Liver Transplantation Recipients. Issue 4 (16th November 2021) - Xiao, Jieling; Yong, Jie Ning; Ng, Cheng Han; Syn, Nicholas; Lim, Wen Hui; Tan, Darren Jun Hao; Tan, En Ying; Huang, Daniel; Wong, Raymond C.; Chew, Nicholas W. S.; Tan, Eunice Xiang Xuan; Noureddin, Mazen; et al.
Abstract : The shift in the changing etiology of cirrhosis requiring liver transplantation (LT) has resulted in an increasing prevalence of coronary artery disease (CAD) that can potentially impact post‐LT outcomes. This systematic review and meta‐analysis evaluates the prevalence of CAD, risk factors, and outcomes of patients diagnosed with CAD before LT. MEDLINE and EMBASE were searched for articles describing CAD in pre‐LT patients. Meta‐analysis of proportions using the generalized linear mix model was conducted to analyze the pooled prevalence of CAD in pre‐LT patients. Associated risk factors for CAD in pre‐LT patients and outcomes were evaluated in conventional pairwise meta‐analysis. A total of 39 studies were included. The pooled prevalence of patients diagnosed with CAD before LT was 15.9% (95% CI, 9.8%‐24.7%). Age, male sex, diabetes mellitus, hypertension, hyperlipidemia, smoking, nonalcoholic steatohepatitis, hepatitis B virus, and hepatocellular carcinoma were significantly associated with CAD. Patients from high‐income countries especially North America, Europe, and South America, with the associated risk factors were at increased risk for CAD before LT. CAD before LT was associated with an increased odds of overall mortality (odds ratio [OR], 1.4; 95% confidence interval [CI], 1.4‐1.4; P  = 0.01) and cardiac‐related mortality (OR, 1.2; 95% CI, 1.1‐1.3; P  = 0.03). A total of 48.7% of included articles considered the presence of cardiovascular risk factors for CAD screening. However, 10.3% of the studies screened for CAD in pre‐LT patients via invasive coronary angiography only, without stress testing or risk stratification. This study demonstrates the high prevalence of CAD in pre‐LT patients, associated risk factors, and outcomes. There is heterogeneity among guidelines and practice in screening for pre‐LT CAD, and more studies are needed to establish consensus.